2009
DOI: 10.3831/kpi.2009.12.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Oriental Medicine Treatment with acupotomy Therpy of the Tarsal tunnel Syndrome

Abstract: In order to estimate clinical effects of Oriental Medicine Treatment with acupotomy therapy of Tarsal tunnel Syndrome Methods : From 5th November, 2008 to 8th November, 2008, 1 male patient diagnosed as Tarsal tunnel syndrome(clinical diagnosed) was treated with general oriental medicine therapy (acupuncture, moxibustion, cupping, physical therapy, herbal medication) and acupotomy. Results : The patient's Rt foot paresthesia, pain were remarkably improved. Conclusions : This study demonstrates that oriental me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…[4,5] Consequently, acupotomy treatment has been applied for various musculoskeletal diseases. [6][7][8][9][10][11] Moreover, in China where acupotomy-related studies are actively being conducted, a total of 36 randomized controlled trials (RCTs) on lumbar disc herniation were published between 2006 and 2016, [12] and 5 RCTs related to lumbar spinal stenosis were reported until 2017. [13] However, in both China and Korea, there is no study on the effects of using both acupotomy and NBT as a combination treatment for lumbosacral radiculopathy.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Consequently, acupotomy treatment has been applied for various musculoskeletal diseases. [6][7][8][9][10][11] Moreover, in China where acupotomy-related studies are actively being conducted, a total of 36 randomized controlled trials (RCTs) on lumbar disc herniation were published between 2006 and 2016, [12] and 5 RCTs related to lumbar spinal stenosis were reported until 2017. [13] However, in both China and Korea, there is no study on the effects of using both acupotomy and NBT as a combination treatment for lumbosacral radiculopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Zhou Han Zhang of China tried this method for the first time by using a therapeutic tool called the small acupotomy, integrating a needle and a knife [ 18 ]. Acupotomy is a therapy to exfoliate synechia by applying a knife shaped needle tip to the synechia around muscles and ligaments [ 27 ]. Once recovered by acupotomy, the synechia is removed and tissues are free to move during activity.…”
Section: Discussionmentioning
confidence: 99%
“…Korean traditional medical treatments for CTS typically include acupuncture, although studies have contradictorily demonstrated the superior and inferior efficacy of acupuncture to placebo or sham acupuncture [ 11 ]. Korean studies of acupuncture for CTS include a randomized control trial (RCT) that compared the effectiveness of Sweet Bee Venom pharmacopuncture to that of Scolopendrid pharmacopuncture, case reports of pharmacopuncture (CA; Scolopendrid , Carthmi-Flos , and Sweet Bee Venom, along with Jungsongouhyul and Hwangryunhaedok-tang pharmacopunctures) and acupotomy, and papers on acupuncture-based treatment [ 12 , 13 ]. Systematic reviews (SR) of Korean medical treatments, including acupuncture, for CTS were conducted [ 11 , 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%